Protocol for LASER: A Randomized Evaluation and an Associated Registry of Early Anticoagulation With Edoxaban After Ischemic Stroke in Patients With Atrial Fibrillation - Alrohimi, Anas; Jickling, Glen; Jeerakathil, Thomas; Shuaib, Ashfaq; Khan, Khurshid; Kate, Mahesh; Hill, Michael D.; Buck, Brian; Butcher, Ken (Frontiers in Neurology, 2021)
Abstract Background: The optimal timing of anticoagulation after stroke in patients with atrial fibrillation (AF) is unknown. Aim and hypothesis: Our primary aim is to demonstrate the safety of edoxaban initiation within five days of AF related stroke. Our secondary aim is to determine predictors of hemorrhagic transformation (HT) after cardioembolic stroke. We hypothesize that the rate of radiological HT will not be increased in patients starting edoxaban within five days of cardioembolic stroke, relative to those in whom initiation is delayed. We hypothesize that the risk of HT in patients treated with edoxaban can be predicted using RNA expressed in leukocytes at time of stroke. Methods and design: LASER (Lixiana Acute Stroke Evaluation Registry) is a randomized controlled trial with an associated registry (clinicaltrials.gov NCT03494530). One hundred and fifty patients with ischemic stroke and AF will undergo baseline Computed Tomography (CT) scan and will be randomized 2:1 within five days of symptom onset to early (≤5 days, n=100) or delayed (6-14 days, n=50) edoxaban initiation. Participants will undergo clinical assessment and repeat CT at 7 days and clinical assessment to 90 days. Study outcomes: The primary outcome is the rate of incident radiological HT. Secondary outcomes include symptomatic HT, recurrent ischemic stroke, recurrent sub-clinical infarcts on follow up CT, systemic hemorrhagic complication rate, National Institute of Health Stroke Scale and modified Rankin Scale at day 7 and 90, mortality within 90 days, quality of life assessments at day 90, and predictors of HT, including RNA expression by 6 pre-selected candidate genes. Discussion: Event rates for both HT and recurrent ischemic events, in patients treated with early versus delayed edoxaban initiation are unknown. The primary study endpoint of LASER is an objective performance criterion relevant to clinical decision making in cardioembolic stroke patients. This study will provide data required for a definitive safety/efficacy study sample size power calculation.